Evaluation of Orofacial and General Pain Location in Patients With Temporomandibular Joint Disorder—Myofascial Pain With Referral - Kuć, Joanna; Szarejko, Krzysztof Dariusz; Sierpińska, Teresa (Frontiers in Neurology, 2019)
Introduction Pain is an emotional experience. As a subjective feeling, it is associated with pathophysiological processes occurring in the central nervous system, which in turn may negatively affect the psychophysical function, cognitive abilities, level of functioning and quality of life. The aim The aim of the study was to assess orofacial and general pain location in patients with temporomandibular joint disorder – myofascial pain with referral. Material and methods The study group consisted of 50 randomly selected, generally healthy people with complete natural dentition (37 women and 13 men) at the age of 23.36 ± 2.14 years, referred to the Department of Prosthodontics of the Medical University. All patients underwent clinical examination according to the Diagnostic Criteria for Temporomandibular Disorders (Axes I and II). The subjects were classified as people with myofascial pain with referral. The evaluation of severity of temporomandibular disorders was based on the Temporomandibular Disorder Pain Screener and the Graded Chronic Pain Scale. In order to assess orofacial and general pain location, a bodychart of pain drawing was used. Results The study group indicated 40 different areas of the body affected by pain. 2-3 isolated pain locations were declared by a total of 6 subjects. One person identified 17 affected areas. 44 people reported pain in at least 4 regions of the body.70% of patients suffered from pain within the right masseter muscle. Pain of the left masseter muscle was noted in 68% of cases. Cervical ailments were reported by 56% of people. Pain of the left temporomandibular joint was observed in 68% of patients, and of the right one in 54%. Conclusion The patients with myofascial pain with referral suffer from general ailments in different regions of the body. Only the frequency of pain in the right masseter muscle and right temporomandibular joint differed with respect to gender. The suggestion that the prevalence of pain in other areas of the body varies between men and women has not been confirmed. Due to a small sample size, such differences cannot be excluded. Further studies in this area are needed.